Emergent hybrid mesophases in ternary mixtures of cellulose nanocrystals ‐ Pluronic micelles‐water. (7th March 2022) - Cohen, Neta; Attia, David; Levi‐Kalisman, Yael; Bitton, Ronit; Yerushalmi‐Rozen, Rachel
Abstract: Mixtures of nanometric rods and spherical micelles that are dominated by excluded volume (entropic) interactions tend to de‐mix into sphere‐ and rod‐rich mesophases. Here we report the observation of hybrid mesophases formed by mixtures of polymer‐decorated sulfuric‐acid‐hydrolyzed cellulose nanocrystals (CNCs, rod‐like particles), at high CNCs concentrations (7 wt%) where the native CNCs suspensions are at the bi‐phasic (isotropic‐chiral nematic) regime, and spherical micelles of the tri‐block‐copolymers Pluronic F127 (and F108) in aqueous suspension. The polymers adsorb onto the CNCs particles, and at F127 concentrations above (10–18 wt%) the macroscopic phases of the hybrid mixture are transformed into mesoscopic droplets with a nanostructure that differs from that of the CNCs or the native Pluronics, as indicated by small‐angle X‐ray scattering. The observed phases preserve the chiral nematic nature of the CNCs phases with a shortened pitch, suggesting that co‐assembly of CNCs and self‐assembling polymers may be used for engineering of emergent phases with emergent structures and properties.